The prokaryotic zinc‐finger: structure, function and comparison with the eukaryotic counterpart. (6th October 2015) - Malgieri, Gaetano; Palmieri, Maddalena; Russo, Luigi; Fattorusso, Roberto; Pedone, Paolo V.; Isernia, Carla
Abstract : Classical zinc finger (ZF) domains were thought to be confined to the eukaryotic kingdom until the transcriptional regulator Ros protein was identified in Agrobacterium tumefaciens . The Ros Cys2 His2 ZF binds DNA in a peculiar mode and folds in a domain significantly larger than its eukaryotic counterpart consisting of 58 amino acids (the 9–66 region) arranged in a βββαα topology, and stabilized by a conserved, extensive, 15‐residue hydrophobic core. The prokaryotic ZF domain, then, shows some intriguing new features that make it interestingly different from its eukaryotic counterpart. This review will focus on the prokaryotic ZFs, summarizing and discussing differences and analogies with the eukaryotic domains and providing important insights into their structure/function relationships. Abstract : The prokaryotic domain, found for the first time in the protein Ros from A. tumefaciens, shows some interesting structural and functional features that differentiate it from its eukaryotic counterpart. The review summarizes and discusses differences and analogies with the eukaryotic domains providing important insights into their structure/function relationships.